Contratos relacionais e o desenvolvimento do mercado de cafés diferenciados: um estudo de caso do setor cafeeiro - Gross, Clarissa Piterman (2012)
This study consists of a case study of contractual relations between the Brazilian company producing coffees, Daterra, and the Italian multinational illycaffè, a roaster focused on the espresso quality coffee market. We start from the relational contract theory as developed by Ian Macneil, and discussed by Ronaldo Porto Macedo Júnior, which considers the contract as a set of practices of exchange projection which involve a multiplicity of economic and non- economic values, as well as recognize the contract normativity as a result of the interconnection between promissory and non promissory sources. We also present the relationship between industrial production models and their importance in promoting more or less relational contractual standards, highlighting the emergence of more relational patterns in a productive context of flexible specialization. The case study proved to be a contractual experience made possible and necessary in the context of international and national coffee market liberalization. Values such as trust, loyalty and knowledge, generated in the course of the contractual relationship, were central in enabling the transition of the entire production chain from the commodity logic to another of differentiated coffee production. The parties design the exchanges through a set of practices, some of a promissory character, others consisting of repeated conducts which generate expectations. The interconnection between these practices creates norms which are shared and consolidated along the continuous interaction between the parties. Moreover, the contractual relationship is dynamic, and we could notice periods of greater and lesser intensity. This dynamic character is also related with changes, over time, in the measure of importance of the values involved in the maintenance of trade between the companies. The case studied was one of the pioneers in the promotion of differentiated coffees production in Brazil, introducing a productive rationality in current expansion in the country. This productive rationality generates more economic, environmental and social value along the production chain and for consumers, and increases the Brazilian coffee growers’ quality of life.